2006
DOI: 10.1136/ard.2005.049924
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of CD4+ CD25high T cell population in patients with systemic lupus erythematosus treated with glucocorticoids

Abstract: Objectives: To characterise and quantify the CD4+ CD25+ T cell population in patients with systemic lupus erythematosus (SLE) and to detect the possible influence of treatments and clinical manifestations. Methods: Characterisation of CD25 low and CD25 high CD4+ T cells from healthy controls and from patients with SLE was carried out using flow cytometry, analysing the expression of activation and differentiation markers. The percentage of both circulating cell subsets was determined in 56 controls and 110 uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 30 publications
(22 reference statements)
5
82
0
5
Order By: Relevance
“…The mean (± SD) percentages of CD4+CD25 bright as well as the total CD4+ CD25+ T cells are in line with the published "normal" values [9,16,17]. CD4+CD25+ T cells have been investigated in several autoimmune diseases, presenting conflicting results in most cases [14][15][16][17][18][19][20][21][22]. These discrepancies may be attributed to the differences in the selection of patients (active or inactive diseases) or probably due to technical difficulties in CD4+ CD25+ T cells phenotypic characterization.…”
Section: Fig (2) Percentages Of Cd4+ Cd25supporting
confidence: 53%
See 1 more Smart Citation
“…The mean (± SD) percentages of CD4+CD25 bright as well as the total CD4+ CD25+ T cells are in line with the published "normal" values [9,16,17]. CD4+CD25+ T cells have been investigated in several autoimmune diseases, presenting conflicting results in most cases [14][15][16][17][18][19][20][21][22]. These discrepancies may be attributed to the differences in the selection of patients (active or inactive diseases) or probably due to technical difficulties in CD4+ CD25+ T cells phenotypic characterization.…”
Section: Fig (2) Percentages Of Cd4+ Cd25supporting
confidence: 53%
“…A recent study done by Azab et al showed that the levels of CD4+CD25+ % T cells in SLE patients were higher than in the control group, but it was statistically insignificant [14]. Also Suárez et al [15] found no significant difference of CD4+CD25+ % T cells between SLE patients and control group. On the other hand, several studies reported a decrease in the percentage of CD4+CD25+ T cells in SLE patients [16,17].…”
Section: Introductionmentioning
confidence: 94%
“…Using CD25 as the identifying marker, initial studies showed that decreased numbers of CD4ϩ,CD25ϩ Treg cells might contribute to the pathogenesis of SLE in humans (9,10). However, recent studies have demonstrated that the numbers of Treg cell subsets, including typical CD4ϩ,CD25 high or CD4ϩ,FoxP3ϩ Treg cells, were not decreased in SLE patients as compared with normal controls (11,12). So far, there have been conflicting reports regarding Treg cell function in lupus patients.…”
mentioning
confidence: 97%
“…Corticosteroid treatment of SLE was associated with increased numbers of Treg [230], while CD25-blocking antibody Daclizumab resulted in decreased Treg numbers in multiple sclerosis that was not related to clinical outcome [231]. In contrast, treatment of rheumatoid arthritis with Infliximab, which blocks the TNF receptor, induced increased frequencies of Treg that did correlate with improved clinical outcome [232].…”
Section: Treg Immunotherapymentioning
confidence: 98%